APLIKASI METODE CONSTANT CURRENT PADA SISTEM PENGISIAN BATERAI LEAD – ACID BERBASIS FAST CHARGING - Ella Metasari; Endah Fitriani (Politeknik Piksi Ganesha Indonesia, 2025)
Air pollution caused by fossil fuel-powered vehicles has a significant impact on public health and the environment, encouraging the transition to electric vehicles in accordance with Presidential Regulation No. 55 of 2019. Electric vehicles use batteries as their main energy source, making a safe charging system essential to prevent overcharging. This study designs a lead-acid battery fast charging system based on the Constant Current (CC) method with a constant current of 2.7 A, equipped with an automatic cut-off. Testing was conducted through field observation, interviews, and literature review. Results show that the charging time is only ±3 hours 13 minutes, significantly faster than the conventional method (10 hours), with component measurements within tolerance limits. The PZEM-017 and voltage divider sensors accurately read voltage according to the datasheet. This system proves to be efficient, safe, and capable of preventing battery damage due to overcharging.